Touchwindow Soluzioni e Sistemi Immersivi per i Beni Culturali. Sistemi e tecnologie per creare spazi dinamici, per coinvolgere, approfondire ed emozionare. - Touchwindow, Touchwindow (Archeomatica, 2014)
Since 1994 the Touchwindow works with diff erent visual and tactile technologies in cultural heritage, off ering advice, solutions and interactive installations in museums and exhibitions. Applications and products Multi-Touch Touchwindow are among the most advanced technological solutions to cr eate unique products, involving installations and memorable visual experience.